Pengembangan Buku Cerita Interaktif Anti-korupsi Berbasis Teknologi Augmented Reality - Pramanta, Febyan Dimas; Hasanah, Uut Uswatun; Kurniawan, Mohammad Rizky (Komisi Pemberantasan Korupsi, 2018)
The issue of corruption has always made headline news in the community. Corruption is very dangerous because can make a big impact in the future. One of the best solutions is to change the behavior with character building, especially on anti-corruption values. Many books have been published to increase the public knowledge and awareness about corruption through the literacy sector. Unfortunately, the interest of reading book in Indonesia is still very low, that is 25,1%. In other side, there are augmented reality technology which is very potential to be developed in the form of anti corruption storybook. This technology can gives the impression for the reader because can show 3D characrter in 2D media. By applying augmented reality technology to the anti corruption storybook, it is expected to improve the quality of education, especially in the field of anti corruption. From the black box test result, this augmented reality application can run its functions as expected.